A THREE-YEAR LONGITUDINAL STUDY OF IN-CLASS SUSTAINED SILENT READING WITH TAIWANESE VOCATIONAL COLLEGE STUDENTS - Ying-ying Hsu; Sy-ying Lee (Indonesian JELT, 2009)
This study examined the effects of three years of in-class sustained silent reading with a group of vocational college students in Taiwan. Readers outperformed comparisons on tests administered after one semester and increased their advantage on tests given at the end of the first year. The gap between the groups narrowed the second year, but readers maintained their superiority at the end of the second and third year. The initial gains were probably due, in part, to the Hawthorne Effect. It is likely that the progress made in the second and third year were more modest, because of external demands on students’ time, which limited the amount of reading students could do outside of class. Overall, the results clearly support the practice of in-school self-selected reading. Keywords:   In-class sustained silent reading; vocational college student; Hawthorne Effect; in-school self-selected reading